Hubungan Tingkat Pemahaman Demokrasi Dalam Pembelajaran PPKn Dengan Toleransi Siswa Dalam Perbedaan Pendapat Kelas X SMK Negeri 1 Sampang - Siti Aisyah; Amir Hamzah; Heni Adhianata (Lembaga Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Keguruan dan Ilmu Pendidikan PGRI Sampang, Indonesia, 2025)
Education is an important aspect of human life that provides many benefits if accessed optimally. As stated in Law of the Republic of Indonesia Number 10 of 2003, which explains that education has a function to develop abilities and shape the character and civilization of a dignified nation. This study aims to explore the relationship between students' level of understanding of democracy obtained from PPKn learning and their tolerance in facing differences of opinion. This study uses a quantitative method with a correlational type. The population in this study was 200 people, with a sample obtained using the Slovin formula of 67 people. The data collection technique used was a questionnaire. Data analysis used in this study included validity tests, reliability tests, normality tests, and correlation tests. Based on the results of the study, it shows that there is a significant relationship between students' level of understanding of democracy and their tolerance towards differences of opinion. From the statistical analysis conducted regarding the understanding of democracy and tolerance of grade 10 students at SMK Negeri 1 Sampang, a Pearson correlation coefficient of 0.260 was obtained with a significance value of 0.034. This means that the higher the students' understanding of democracy, the higher their level of tolerance towards differences of opinion.